Oil prices and stock markets: What drives what in the gulf corporation council countries? - Mohamed El Hedi Arouri; Christophe Rault (Center for Economic Studies and ifo Institute (CESifo), 2010)
In the empirical literature, only few studies have focused on the relationship between oil prices and stock markets in net oil-importing countries. In net oil-exporting countries this relationship has not been widely researched. This paper implements the panel-data approach of Kónya (2006), which is based on SUR systems and Wald tests with country-specific bootstrap critical values to study the sensitivity of stock markets to oil prices in GCC (Gulf Corporation Council) countries. Using two different (weekly and monthly) datasets covering respectively the periods from 7 June 2005 to 21 October 2008, and from January 1996 to December 2007, we show strong statistical evidence that the causal relationship is consistently bi-directional for Saudi Arabia. Stock market price changes in the other GCC member countries do not Granger cause oil price changes, whereas oil price shocks Granger cause stock price changes. Therefore, investors in GCC stock markets should look at the changes in oil prices, whereas investors in oil markets should look at changes in the Saudi stock market.
Keywords: G12; F30; Q43; 330; GCC stock markets; oil prices; Börsenkurs; Aktienmarkt; Erdölpreis; Panel; Kointegration; Schätzung; Arabische Golf-Staaten